What are Polish women afraid of in vaginal birth? – A Cross-Sectional Study - Walasik, Izabela; Kosińska-Kaczyńska, Katarzyna; Kwiatkowska, Katarzyna; Roman, Natalia; Wysińska, Julia; Szymusik, Iwona (Journal of Medical Science, 2020)
Introduction. Fear of childbirth is a specific feeling related to approaching birth that ranges from negligible to very intense. Women’s choices and doubts regarding the way of birth may be related to a lack of knowledge about the benefits and advantages of VB or a fear of this method of childbearing.Aim. The aim of the study was to assess knowledge regarding labour, its possible complications and ways to prepare for vaginal delivery among Polish womenMaterial and Methods. A cross-sectional study was performed among 4721 women who were pregnant or who had had at least one delivery. A self-composed questionnaire was distributed via the internet in 2018.Results. It seems that 13.9% of the respondents were pregnant, 49.2% women gave birth vaginally and 30.8% had a caesarean delivery. Most of the respondents were afraid of the pain associated with the labour (75% pregnant women, 63.4% women after vaginal birth, 59.1% women after caesarean section), and 57.8% of respondents would like to avoid episiotomy, but only 27,5% of them used any methods of perineal protection for vaginal delivery. Also, 43.4 % of respondents believe that vaginal delivery may have a negative impact on satisfaction in their sexual life, 26% of respondents think that a caesarean section scar has no impact on subsequent pregnancies, and 41% claim that women who had a caesarean delivery feel discriminated against as a cesarean section is considered to be a labour failure in society.Conclusions. Women’s knowledge on the advantages and risks related to the methods of labour is insufficient, which may affect their preferences regarding vaginal or cesarean birth.
Keywords: vaginal delivery; cesarean section; fear of childbirth